2014
DOI: 10.1161/hypertensionaha.113.01866
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Mesylate Attenuates Myocardial Remodeling Through Inhibition of Platelet-Derived Growth Factor and Transforming Growth Factor Activation in a Rat Model of Hypertension

Abstract: The spontaneously hypertensive rat (SHR) is a genetically hypertensive rat model used to study human essential Abstract-Imatinib mesylate is a specific tyrosine kinase inhibitor that may block the platelet-derived growth factor and transforming growth factor pathways. These pathways are known to provoke fibroblast activation. We evaluated whether imatinib, by inhibiting these pathways, prevents diastolic dysfunction and attenuates myocardial remodeling using spontaneously hypertensive rats (SHRs). Eight-week-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…As a classical tyrosine kinase inhibitor, IMA inhibits the kinase activation of PDGFRs, c-Kit and c-Abl [14]. Recent studies demonstrated that the mechanisms of inhibition fibrosis by IMA were associated with blocking the activation of PDGFRs, and c-Abl [1820]. Our results showed that IMA inhibited the activation of PDGFRα and PDGFRβ and decreased the mRNA expression of TGF-β1.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…As a classical tyrosine kinase inhibitor, IMA inhibits the kinase activation of PDGFRs, c-Kit and c-Abl [14]. Recent studies demonstrated that the mechanisms of inhibition fibrosis by IMA were associated with blocking the activation of PDGFRs, and c-Abl [1820]. Our results showed that IMA inhibited the activation of PDGFRα and PDGFRβ and decreased the mRNA expression of TGF-β1.…”
Section: Discussionsupporting
confidence: 58%
“…Many animal models have been used for the research of cardiac fibrosis, such as spontaneously hypertensive induced cardiac fibrosis model [18], the surgery models (myocardial infarction model, myocardial ischemia/reperfusion injury model, and transverse aortic constriction model) [45], and the induced models (desoxycorticosterone induced salt-sensitive hypertensive model [19], Ang II induced cardiac fibrosis model [46], and ISO induced cardiac fibrosis model [10]). However, the mechanisms of cardiac fibrosis in different models are diverse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other possibilities such as a direct effect of angiotensin II (ANG II) on the gut cannot be ruled out. ANG II has been shown to induce fibrosis and hypertrophy of vessels and heart tissue in rodent models of HTN [43], and these pathologies are also present in the SHR model [44]. Finally, changes in the gut may be indirect and could be induced by increase in blood pressure.…”
Section: Resultsmentioning
confidence: 99%